The Accounting Practices and the Sustainability of Merchandising Businesses in the Municipality of Bulan, Sorsogon, Philippines - Bongalonta, Atty. Michael B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Long-term viability of local enterprises may be affected by financial management behaviors of its owners. It is in this premise that this study was conducted among merchandising businesses in Bulan, Sorsogon. This study examined the accounting and sustainability of these merchandising enterprises to determine and assess accounting practices, identify and assess sustainability, and establish the relationship between accounting practices and sustainability. Correlational research design and mixed-method approach were utilized. Quantitative and qualitative data were gathered and analyzed to gain comprehensive understanding of the phenomenon. Descriptive statistics, path analysis, and structural equation modeling were used to evaluate the direction of relationships between variables. The findings revealed that among merchandising businesses in Bulan, Sorsogon the accounting practices were practiced in an inconsistent manner. The most consistently done among these businesses were inventory management and record keeping. Data shows that conducting business in a manner that leads toward sustainability was practiced “sometimes”. Moreover, inventory management and record keeping had highest positive and significant effects on sustainability as shown by path analysis. SEM further verified this strong relationship. The study reveals that merchandising enterprises that are more systematic also exhibit higher resilience, financial stability and environmental responsibility.